مساهمة الإتصال التسويقي في دفع السلوك الشرائي للمستهلك دراسة على مستخدمي موقع jumia الإلكتروني - قناوي أحلام; قناوي رحمة (My University, 2022)
Abstract: The study titled "The Contribution of Marketing Communication in motivating the Consumer Purchasing Behaviour within Jumia Algeria web site users" tackles the status and impact of marketing communication in the consumers behaviour motivation and influence. The study investigates marketing communication contribution in customer behaviour motivation in order to buy product swithin Jumia Algeria web site through highlighting the significance of marketing communication as a funda mental task in linking the virtual site Jumia and clients. Substantially its role and impact is identified and the impact of the consumer interaction with the site is determined. Additionally, the study determines the habits of the consumer dealing with the site, clarifying the reasons behind usingit and determining the satisfactory results achieved. The refore, the descriptive method as a suitable. , and the survey method for the analysis method to the research questions isused. Data in the practical part were gathered through an electronic questionnaire as a tooldirected to users of Jumia Algeria web site. Subsequently,76response subject to analysis and study were collected. Analysing the statics and replying the sub-questions of the practical study; the study concludes that marketing communication contribution in influencing the consumer purchasing behaviour as it uses a well practically and scientifically structured pre-studiedtools. Jumia Algeria has contributed witha medium rate in influencingits agents through creating an effective and harmonic communicative mixture that achieved the intended effect. The study on the Algerian web site recommended to pay more attention to interacting with clients in order to establish a keenmanaged relationship. -------------------------------- ملخص الدراسة بعنوان "مساهمة الاتصالات التسويقية في دوافع سلوك الشراء لدى المستهلكين بين مستخدمي موقع "جوميا الجزائر" يتناول حالة وتأثير الاتصال التسويقي في دوافع وتأثير سلوك المستهلك. لفهم تأثير تعرض المستهلك للمنصة "جوميا"، وبالتالي معرفة تقاليد المعرض في هذا الموقع وأسبابه ولإستخدامه استخدمنا المنهج الوصفي نظرا لخصائصه التوافق مع مشكلتنا وطريقة التحقيق بالتحليل . لقد استخدمنا أيضًا المسح الإلكتروني كأداة لـ جمع البيانات في الجزء العملي الذي كان مخصصًا لمستخدمي موقع جوميا الجزائر. لقد تلقينا 76 ردًا للتحليل. بعد المعالجة الإحصائية والإجابات على الأسئلة الثانوية التي تم جمعها العلاقة مع محاور الدراسة الميدانية نصل إلى القول بأن يؤثر الاتصال التسويقي على سلوك الشراء لدى المستهلك لأنه يعتمد على مجموعة من الأدوات والعناصر المنظمة والمدروسة نظريا وعمليا. بالإضافة إلى ذلك، تلعب الاتصالات التسويقية دورًا مهمًا في موقع Jumia DZ وأن هذا التواصل يتعلق بالعلاقة بين الموقع وعملائه و يهدف إلى تعزيزه. ----------------------------- Résume L'étude intitulée "La contribution de la communication marketing dans la motivation du comportement d'achat des consommateurs chez les utilisateurs du site Jumia Algérie" aborde le statut et l'impact de la communication marketing dans la motivation et l'influence du comportement des consommateurs. Pour connaitre l’effet de l’exposition du consommateur à la plateforme ‘’Jumia’’, ainsi connaitre les traditions de l’exposition à ce site et les motifs derrière son utilisation, nous avons utilisé la méthode descriptive vu sa compatibilité avec notre problématiquez et La méthode d'enquête par analyse . Nous avons aussi fait recours au sondage électronique comme outil pour collecter les données dans la partie pratique qui a été destinée aux utilisateurs du site ‘’Jumia Algérie’’. Nous avons reçu 76 réponses à analyser. Après le traitement statistique et les réponses aux questions secondaires qui ont une relation avec les axes de l’étude sur terrain, nous arrivons à dire que la communication marketing influence le comportement d’achat du consommateur parce qu’il repose sur un ensemble d’outils et éléments organisés et étudiés théoriquement et pratiquement. En outre, la communication marketing a un rôle important dans le site Jumia DZ et que cette communication s’intéresse à la relation entre le site et ses clients et vise à la consolider.
Keywords: المساهمة، الاتصالات التسويقية، سلوك الشراء، مستهلك.